Como andam os pés dos idosos... Dificuldades e repercussões - Nagy, Istvan (2006)
The general purpose of this investigation is to search for parallels between the causes of some of the most important physical, psychic and behavioral problems of old age and those of foot deformities. The extent to which such foot abnormalities exert an influence on the quality of life of aged people has a direct bearing on the matter under discussion. This study aims at gathering supporting evidence for the analysis of the obstacles old people face in their social commitments when they have defective feet to cope with. Aging entails deleterious anatomical and physiological changes characterizing distinct diseases, which include those affecting the feet. This can cause people to keep away from socio-cultural activities. The feet do not usually receive the same attention as other parts of the body until callosities or odors start to bother. Old people only mention their feet when these are hurting. However, it is nonsensical to keep such problems hidden within the shoes. There are clinical and surgical interventions which can correct one s way of walking and even adjust the anatomical position of the toes. Thus, old people should seek help from health professionals to prevent any worsening of the condition of their feet, which often give us the first indications of serious medical conditions such as the arthritis, diabetes, nervous system and circulation problems. Morphological or physiological alterations occurring in people can, over the long run, involve undesirable consequences in connection with behavior, intellectual ability and physical capacity to proceed with their normal activities. In such cases the feet obviously play, directly or indirectly, an important role in one s eventual inclusion or exclusion in groups which could promote social interactions. After all, as aged people restrict their movements, they start a vicious cycle: reduced activities (sedentary life) lead to muscular atrophy, weakness of the legs and consequently the avoidance of social activities. To solve the problem of the insertion of old people in the social context, the help of health professionals, including physiotherapists, gerontologists, and clinicians amongst others, is essential. Such professionals should harmoniously cooperate to reach a common objective. Some kinds of implements are used to successfully fulfill the purposes which are a good quality of life and longevity